GREENWASHING AS CONTRACTUAL FRAUD: EXAMINING ITS LEGAL IMPLICATIONS AND IMPACT ON CONTRACT VALIDITY UNDER INDONESIAN LAW - Prisandani, Ulya Yasmine (Diponegoro Law Review, 2025)
Greenwashing, the practice of making false or exaggerated environmental claims to deceive consumers, has emerged as a pressing issue in various industries. This study explores the legal implications of greenwashing under Indonesian law, particularly its impact on the validity of contracts. Utilizing a normative legal research methodology, this paper examines the gap in Indonesian regulations regarding greenwashing, highlighting its connection to deceptive marketing and contractual fraud. According to the Indonesian Civil Code, contracts are only valid if there is mutual consent between the parties. Greenwashing, by distorting the truth about a product or service's environmental impact, undermines this essential element of consensus, potentially rendering contracts voidable. This research draws parallels between greenwashing and contractual fraud, explaining how deceptive claims can mislead parties, disrupting their agreement and affecting the contract’s legitimacy. Furthermore, the paper analyzes how greenwashing can be classified as fraud under the Indonesian Criminal Code, with implications for both civil and criminal liability. Despite the lack of specific regulations addressing greenwashing, the study proposes that its deceptive nature should be treated as a distinct legal issue, separate from general fraud. It also emphasizes the need for legal reforms to protect consumers and ensure that companies are held accountable for their environmental claims. The study concludes by advocating for stricter regulations and oversight mechanisms to mitigate the environmental and financial harm caused by greenwashing in Indonesia.